Antidepressant-like Effects Induced by Chronic Blockade of the Purinergic 2X7 Receptor through Inhibition of Non-like Receptor Protein 1 Inflammasome in Chronic Unpredictable Mild Stress Model of Depression in Rats - Aricioglu, Feyza (Clin Psychopharmacol Neurosci, 2019)
OBJECTIVE: Purinergic 2X7 receptor (P2X7R) activation is known to be involved in pathogenesis of depression. Our aims were to investigate P2X7R-activated inflammasome pathways in parallel with induction of depression and to test the antidepressant-like effects of the selective P2X7R antagonist Brilliant Blue G (BBG) in a rat model of chronic unpredictable mild stress (CUMS). METHODS: Male Wistar albino rats were divided into control, CUMS, CUMS+BBG25 (25 mg/kg/day) and CUMS+BBG50 (50 mg/kg/day) groups (n=10 for each group). Various stressors were applied to rats for 6 weeks to establish the CUMS model and daily BBG treatment was started at the end of 3rd week. Sucrose preference test and forced swim test (FST) were performed to assess antidepressant-like effects. Brain samples were obtained for real-time polymerase chain reaction and immunohistochemistry analysis. RESULTS: In FST, duration of immobility was reduced in the CUMS+BBG50 group. Also, BBG treatment significantly enhanced sucrose preference. While NLRP3 gene expression levels were unchanged in rats exposed to the CUMS protocol, expression levels of other inflammasome pathway factors NLRP1, caspase-1, ASC, NF-κB, IL-1β, IL-6 and P2X7R were increased. BBG treatment reduced expression levels of these factors. Likewise, Iba-1 and GFAP immunoreactivities were enhanced by the CUMS protocol and this action was reversed by BBG treatment. CONCLUSION: Chronic administration of BBG in CUMS model results in antidepressant-like activity in a dose dependent manner. Molecular and histological results show that these effects might be at least partially related to the suppression of inflammasome-related neuroinflammatory responses and suggest involvement of NLRP1 in depression.